The image of a kindergarten teacher in the israeli media - Alezra, Fani (Rocznik Pedagogiczny, 2019)
Recognition of the importance of early childhood education is increasing. Many reports published in Israel and around the world deal with the powerful and critical impact of this era on individuals and society. In contrast, the professional image of the kindergarten teacher in Israel is seen as be- ing as low-status as in many countries. This professional image influences the choice of teaching profession and the conditions of admission in teacher training colleges. The low-status image is influenced by many publications in the Israeli media. To say these publications are unflattering to the profession and to kindergarten teachers would be an understatement. In this article, I will try to answer the question: How is the kindergarten teacher’s image expressed in publications about kin- dergarten and kindergarten teachers in the media in Israel? The research tools are ten articles with the kindergarten tag on the news content sites Walla and Mako as of June 2019. The method chosen is content analysis, a research technique for objectively describing media content through which messages can be identified. In so doing, I will draw conclusions about what can be done to improve publications about the profession and at the same time to improve the image of the kindergarten teacher in society.